PENERAPAN MODEL PEMBELAJARAN QUESTION STUDENT HAVE DALAM MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN SEJARAH KEBUDAYAAN ISLAM KELAS X.2 MAN 1 KOTA MAKASSAR - Adrian; Mustamin; Raehana, Syarifah; Wahab, Abdul; Azhar, Muh (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Islamic history classes can easily slide into one-way lecturing, and that was largely the case in Class X.2 at MAN 1 Kota Makassar, where students absorbed material passively rather than questioning it reflected in pre-cycle scores averaging just 68.33, with only 36.1% of the 36 students meeting the minimum mastery criterion. This study examined how the Question Student Have model, in which students write down their own questions rather than wait to be asked, could be applied to Islamic Cultural History instruction and whether doing so would raise learning outcomes. Framed as classroom action research across two cycles, it drew on 36 Grade X students together with their subject teacher, gathering data through observation, semi-structured interviews, achievement tests, and documentation, then analyzing the results descriptively via mean scores and mastery percentages. Once the model was introduced, engagement and results moved together: the class average rose to 79.86 with 61.1% mastery after Cycle I, then reached 90.55 with 86.1% mastery by Cycle II comfortably clearing the study's success benchmarks. The findings suggest that letting students set the questions, rather than only answer them, is a workable way to lift both participation and achievement in Islamic Cultural History classrooms